Halal pharmaceutical industry in Nigeria: a bitter pill to Swallow / Carrie Amani Annabi and Suhayr Mustapha Wada. - Annabi, Carrie Amani; Wada, Suhayr Mustapha (Universiti Teknologi Mara Selangor, 2016)
Notwithstanding Nigeria’s large Muslim population of 89.25 million citizens, very little research has been carried out in terms of addressing Halal needs in Nigeria. This qualitative case study reviewed the perspective of 32 respondents, (15 patients, 15 doctors and two pharmacists), in a medical centre in Abuja, Nigeria on their perceptions on and awareness of Halal pharmaceuticals. The interview data were collected through telephone interviews. Data analysis and findings were examined against the literature reviewed in this study. Findings concluded that there was a lack of awareness of Halal medicine products within Nigeria and that this was the primary reason why the respondents felt that there was a dearth of Halal pharmaceuticals. There were also secondary concerns from the patients about the risk of counterfeit medicine and the doctors were worried at the potential cost of providing Halal pharmaceutical options in case it deterred patients from buying the (Halal) medicaments prescribed. The pharmacists were supportive of Halal pharmaceuticals in principle but highlighted issues surrounding both the efficacy of alternatives and the effectiveness of some current ingredients that might be deemed unacceptable in Halal preparations.